Multichannel EEG with novel Ti/TiN dry electrodes - Fiedler, P. (2015)
Research using multichannel electroencephalographic recordings is increasingly characterized by greater numbers of electrodes. With up to 256 silver/silver chloride (Ag/AgCI) electrodes, preparation and electrode placement is time consuming and error prone. We propose a novel type of dry titanium/titanium nitride (Ti/TiN) electrode, integrated into a novel electroencephalography (EEG) cap based on pneumatic-driven mechanisms. The electrodes were characterized electrochemically and comparative biosignal measurements were carried out. In a NaCl solution, the impedance values were between 824 and 54 ohm and the phase values between 52 and 100 at frequencies between 5 Hz and 10 kHz for the Ti/TiN electrodes. For resting-state EEG, and with eye movements, alpha activity, and pattern reversal visual evoked potential (VEP), there were no significant differences between adjacent novel Ti/TiN and standard Ag/AgCI electrodes in 97.2% of the signal episodes investigated. The potential maps for pattern reversal VEP were similar with both types of electrodes. In conclusion, our novel cap system based on Ti/TiN electrodes and pneumatic-driven mechanisms enables completely dry EEG acquisition and can thus potentially replace conventional Ag/AgCI electrodes due to similar signal quality.